![-3x+y=-2 \\ y-4=-6x \ \ \ |\times (-1) \\ \\ -3x+y=-2 \\ \underline{-y+4=6x} \\ -3x+y-y+4=6x-2 \\ -3x+4=6x-2 \\ -3x-6x=-2-4 \\ -9x=-6 \\ x=\frac{-6}{-9} \\ x=\frac{2}{3} \\ \\ y-4=-6 \times \frac{2}{3} \\ y-4=-4 \\ y=-4+4 \\ y=0 \\ \\ (x,y)=(\frac{2}{3},0)](https://tex.z-dn.net/?f=-3x%2By%3D-2%20%5C%5C%0Ay-4%3D-6x%20%5C%20%5C%20%5C%20%7C%5Ctimes%20%28-1%29%20%5C%5C%20%5C%5C%0A-3x%2By%3D-2%20%5C%5C%0A%5Cunderline%7B-y%2B4%3D6x%7D%20%5C%5C%0A-3x%2By-y%2B4%3D6x-2%20%5C%5C%0A-3x%2B4%3D6x-2%20%5C%5C%0A-3x-6x%3D-2-4%20%5C%5C%0A-9x%3D-6%20%5C%5C%0Ax%3D%5Cfrac%7B-6%7D%7B-9%7D%20%5C%5C%0Ax%3D%5Cfrac%7B2%7D%7B3%7D%20%5C%5C%20%5C%5C%0Ay-4%3D-6%20%5Ctimes%20%5Cfrac%7B2%7D%7B3%7D%20%5C%5C%0Ay-4%3D-4%20%5C%5C%0Ay%3D-4%2B4%20%5C%5C%0Ay%3D0%20%5C%5C%20%5C%5C%0A%28x%2Cy%29%3D%28%5Cfrac%7B2%7D%7B3%7D%2C0%29)
The system has one solution so it's
A. consistent and independent.
Answer:
x≥4
Step-by-step explanation:
We want to solve for x in
![2x - 3 \geqslant 5](https://tex.z-dn.net/?f=2x%20-%203%20%5Cgeqslant%205)
Let us add 3 to both sides:
![2x - 3 + 3\geqslant 5 + 3](https://tex.z-dn.net/?f=2x%20-%203%20%20%2B%203%5Cgeqslant%205%20%2B%203)
We simplify to get:
![2x\geqslant 8](https://tex.z-dn.net/?f=2x%5Cgeqslant%208)
Divide through by 2 to get:
![x \geqslant 4](https://tex.z-dn.net/?f=x%20%20%5Cgeqslant%204)
Answer:
Step-by-step explanation:
Answer:
wheres the expression
Step-by-step explanation:
Each heir would receive $20727.27